Europe and South-East Asia: An exercise in diplomatic patience - Hanna Deringer; Hosuk Lee-Makiyama (European Centre for International Political Economy (ECIPE), 2018)
The EU is hoping to revive the negotiations for a region-to-region agreement with the Association of South-East Asian Nations (ASEAN), but few trading partners have faced such inauspicious fate as its members. The trade agreement with Singapore is concluded but remains unsigned and the EU Member States do not seem to be in a hurry to ratify the EU-Vietnam agreement due to the prospects of rejection by the European Parliament over labour issues. There is a proposal by the European Parliament to effectively stop the use of palm oil in biodiesels under the new Renewable Energy Directive (RED-II), which has caused Malaysia, Indonesia and Thailand to threaten trade retaliation against multiple EU exporters and the termination of both bilateral and regional trade negotiations. Given existing jurisprudence any such differentiated treatment or selective exclusion of one crop would not comply with WTO law, exposing the EU to a time-consuming WTO dispute. Moreover, military rule in Thailand, reports of human rights violations in the Philippines under President Duterte or atrocities in Myanmar will inevitably complicate both bilateral and EUASEAN negotiations. In Europe, much of the policy work undertaken in the current political term is dedicated to restoring the mandate and win back public trust for trade policy. The EU is weakened politically and has little wriggle room for concessions internally. The EU is demanding more, while offering less, in its international negotiations. The European Parliament shifts EU trade policy towards unilateral and short-term interests rather than a trade policy that could enable long-term political reforms and support the EU's long-term geo-economic interests. Europe's engagement with the ASEAN countries and the promotion of WTO rules, human rights and sustainability calls for a long-term approach which requires patience.
Keywords: 330